PENINGKATAN PEMBELAJARAN TEMATIK TERPADU DENGAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SD - WARIZONA, DOLI OKTASEDA (Universitas Negeri Padang, 2014)
abstracThe aim of this research was to improve the integrated thematic learning by using PBL model on My Environment topic in grade IV of SD Negeri 01 Pauh Kuraitaji Kota Pariman. The subject of the research was teacher and 17 student. The result of the research was the cycle I to cycle II, the score oh the Lesson Plan Increased from 80.4% to 90.8%, the students aspect increased from 80.4% to 92.8%. Key Terms: thematic learning process, Problem Based Learning